RELEVANT BIOCHEMICAL INDICES OF BLOOD RADIOSENSITIVITY IN GYNECOLOGICAL CANCER PATIENTS - Domina, E A; Makovetska, L I; Druzhyna, M O (Problemy radiatsiinoi medytsyny ta radiobiolohii, 2022)
identification of the relevant biochemical indices of blood radiosensitivity in endometrial cancerpatients under the test irradiation in a wide range of doses. Peripheral blood samples were drawn for assay in the newly diagnosed endometrial cancer patients (study group, n = 42) and healthy donors (control group, n = 27). A set of biochemical values was reviewed to identify and justify the prognostic markers of cell radiosensitivity in the tumor environment featuring gradual development of oxidative stress, namely the intensity of superoxide anionradical (О2) generation, pro/antioxidant ratio (PAR), and malondialdehyde (MDA) content. Predictive values were selected through the construction and analysis of «doseresponse» dependencies of the studied parameters during Xray test exposure in a dose range of 0.5-3.0 Gy. Nature of the dose curves was determined using linear and linearquadratic regression models. The 3.2 times higher MDA content was found in blood plasma of endometrial cancer patients compared to the control group, namely (60.87 ± 4.93) μM/g of protein versus (18.93 ± 2.05) μM/g of protein (р ≤ 0.05). The raise in MDA content along with increase in the test radiation dose (in a range of 0.5-3.0 Gy) was approximated by the linear regression model Y = 67.44 + 12.52D, R2 = 0.85. A 1.29-1.74fold increase in the mean group value depending on the radiation dose was recorded (р ≤ 0.05). Effects of lowdose irradiation (0.5 Gy) were differentiated as (85.03 ± 8.9) against the initial MDA level of (60.87 ± 4.93) μM/g of protein. There was an increase in the intensity of О2 generation in blood lymphocytes and elevated PAR value in hemolysate from endometrial cancer patients compared to healthy donors by 1.34 and 1.30 times (р ≤ 0.05) respectively, which indicated the intensification of prooxidant processes in patients. The interindividual peculiarities of the blood reactionresponse to radiation were revealed according to parameters depending on the initial values, which characterize them only as additional prognostic biomarkers in radiation treatment planning for gynecological cancer patients. It has been proven that the linear nature of dose dependence of MDA content in blood plasma of endometrial cancer patients and response to lowdose irradiation of are the basic criteria for recognizing MDA as a relevant prognostic biochemical indicator of radiosensitivity of healthy cells from the tumor environment. The content of MDA in blood plasma of gynecological cancer patients should be taken into account in order to identify the subjects with a high risk of radiation complications.